1973
DOI: 10.1007/bf00036657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breeding semidwarf rice by induced mutation and hybridization

Abstract: Semidwarf indica varieties of rice (Oryza sativa L.) were developed by induced mutation. They generally have a yield capacity equal to that of the semidwarf varieties (T(N)1, IR 8 and others) selected from hybridization . Genetic studies showed that semidwarf genes induced in the mutants and spontaneous ones in existing varieties are at the same locus . These semidwarf mutants, selected in Taiwan and from an American long-grain variety, Centura Patna 231, were compared with their parents, the semidwarf variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…In other genotypes of this group the grain size is reduced. In some mutants the dwarfism is combined with earliness (Hu 1973) or with an increased protein content (Misra et al1971). In Japan, ten promising mutant lines with stiff straw, high yield, and excellent cooking quality of the grain were selected from a mother variety with low lodging resistance (Samoto 1975).…”
Section: Ricementioning
confidence: 99%
See 2 more Smart Citations
“…In other genotypes of this group the grain size is reduced. In some mutants the dwarfism is combined with earliness (Hu 1973) or with an increased protein content (Misra et al1971). In Japan, ten promising mutant lines with stiff straw, high yield, and excellent cooking quality of the grain were selected from a mother variety with low lodging resistance (Samoto 1975).…”
Section: Ricementioning
confidence: 99%
“…In Japan, ten promising mutant lines with stiff straw, high yield, and excellent cooking quality of the grain were selected from a mother variety with low lodging resistance (Samoto 1975). Thus, it may be possible to grow one more crop within a year in the respective regions (Hu 1973). The best short-culm mutant of a French collection had a better lodging resistance and a 50% increased yield, but the plants were 6 days later and the milling quality of the grains was insufficient (Marie 1967).…”
Section: Ricementioning
confidence: 99%
See 1 more Smart Citation
“…Genotypes with a dominant allele are photoperiod sensitive, and homozygous recessive genotypes are insensitive. Some workers have reported a positive association between photoperiod sensitivity and plant height (RAMIAH, 1933;ESCURO, 1960;Hu, 1973). Some workers have reported a positive association between photoperiod sensitivity and plant height (RAMIAH, 1933;ESCURO, 1960;Hu, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Some cases of recessive alleles conditioning photoperiod sensitivity have been reported (SAMPATH & SESHLJ, 1961;KLJRIYAMA, 1965;SIMBE, 1982). Hu (1973) suggested that the genes inducing short stature may confer insensitivity to photoperiod. Hu (1973) suggested that the genes inducing short stature may confer insensitivity to photoperiod.…”
Section: Introductionmentioning
confidence: 99%